Crassocephalum crepidioides as a sustainable protein supplement in Chocolatemahseer (Neolissochilus hexagonolepis) diets: Implications for growth,health, and economic viability in sustainable aquaculture - DEBNATH, CHANDAN (The Indian Journal of Animal Sciences, 2024)
This study investigated the potential of Crassocephalum crepidioides, an abundant weed as a protein supplement in chocolate mahseer (Neolissochilus hexagonolepis) diets. The plant replaced a combination of fish meal and mustard oil cake at 0%, 25%, 50%, 75%, and 100% in experimental diets. A 12-week feeding trial was conducted to assess growth performance, survival, biomass yield, digestive enzyme activity, blood parameters, and economic viability. Results indicated that C. crepidioides can effectively replace up to 61.3% of the combined fish meal and mustard oil cake protein without negatively impacting fish health or growth, while reducing feed costs. Fish fed diets with 25% replacement showed improved weight gain (15.5±0.7 g) and biomass yield (6.05±0.25 kg/m³) compared to the control (14.6±0.8 g and 5.75±0.28 kg/m³, respectively). Survival rates were high across all treatments (94.0- 97.3%). Digestive enzyme activities and blood parameters remained within normal ranges for inclusion levels up to 75%. Economic analysis revealed potential cost savings of up to 15.5% when incorporating C. crepidioides into mahseer diets. This finding presents an opportunity to develop low-cost fish feed for resource-poor farmers in Meghalaya, effectively converting a local weed into a valuable aquaculture input, with broader implications for sustainable aquaculture practices globally.